1963
DOI: 10.1083/jcb.17.3.465
|View full text |Cite
|
Sign up to set email alerts
|

A Histochemical Study of Phagocytic and Enzymatic Functions of Rabbit Mononuclear and Polymorphonuclear Exudate Cells and Alveolar Macrophages

Abstract: The cytochromc oxidasc (CO), aminopcptidasc (AMP), succinic dchydrogcnasc (SD), acid phosphatasc, cstcrasc, and alkaline phosphatasc of rabbit mononuclcar (MN) and polymorphonuclcar (PMN) peritoneal cxudatc cells and pulmonary alveolar macrophagcs (AM) -air dried on Mylar strips-were characterized by histochcmical techniques with respect to stability, activators, inhibitors, and pH optima. A granule count method was established for the quantitation of these cnzymcs. For the acid phosphatasc of MN, in which the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

1969
1969
1998
1998

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(44 citation statements)
references
References 76 publications
(88 reference statements)
3
41
0
Order By: Relevance
“…These cells have high levels of endogenous ␤-galactosidase. [40][41][42][43] In particular, infiltrating lymphocytes which contain large amounts of lysosomal ␤-galactosidase [40][41][42] are abundant in infarcted myocardium, but are absent within normal myocardium. Although liposomes can activate macrophages directly to increase the activity of a membranous ␤-galactosidase, 44 this would not explain the macroscopic appearance we observed after coil occlusion.…”
Section: Figure 5 the Macroscopic Appearance Of A Heart 3 Days Followmentioning
confidence: 99%
“…These cells have high levels of endogenous ␤-galactosidase. [40][41][42][43] In particular, infiltrating lymphocytes which contain large amounts of lysosomal ␤-galactosidase [40][41][42] are abundant in infarcted myocardium, but are absent within normal myocardium. Although liposomes can activate macrophages directly to increase the activity of a membranous ␤-galactosidase, 44 this would not explain the macroscopic appearance we observed after coil occlusion.…”
Section: Figure 5 the Macroscopic Appearance Of A Heart 3 Days Followmentioning
confidence: 99%
“…The tumor cell suspension was then injected subcutaneously into the right flank of mice (106 cells/mouse), and the tumor growth in mice was observed for 6 weeks (3,4). In addition, the number of viable Ehrlich tumor cells was examined by the trypan blue test after incubation in the presence or absence of pentazocine, and the proportion of the viable tumor cells was calculated from the number of viable and dead cells (5). Examination of antitumor activity of pentazocine:…”
Section: Tumor Cell Suspensionmentioning
confidence: 99%
“…In turn, the alteration of enzyme patterns leads to a more suitable bioenergetic pattern as a function of 02 availability. (7). Ultrastructural studies have shown the AM to have greater numbers of mitochondria and increased density of cristae than the PM (8).…”
mentioning
confidence: 99%